Effects of CeO2/Y2O3 rare earth oxides on microstructure and properties of in-situ synthesized WC-reinforced Ni-based cladding layer - Zhang C. X.; Sun W. C.; Liu E. Y.; Liu Y. W.; Liu J. P.; Zhang B.; Xu Y. F.; Zhou M. R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A novel tungsten carbide (WC)-reinforced nickel (Ni)-based laser cladding layer was prepared through an in-situ synthesis process. The influence of different concentrations of CeO2/Y2O3 on the microstructure, wear, and corrosion resistance of the in-situ synthesized WC-reinforced Ni-based cladding layer was analyzed. The results revealed that the coatings doped with rare-earth oxides exhibited good micro-hardness (660 HV0.2) and wear resistance when the rare-earth oxide content reached 0.75% CeO2 and 1.50% Y2O3. Additionally, the minimum corrosion rates of the coating were measured at 0.002770 mm/a and 0.0022548 mm/a at 1.5% CeO2 and 1.5 Y2O3 doping, with noble Ecorr values ranging from -0.12549 V to -0.49924 V and lower Icorr values ranging from 2.3550×10-7 A·cm2 to 1.9170×10-7 A·cm2. Furthermore, the wear resistance of the cladding layer was significantly higher than that of the substrate. Both the cladding layer and the substrate exhibited a mixed-wear mode, and they exhibit adhesive wear in wet friction environments.